The nutritive, rheological and sensory quality of selected indigenous complementary foods used for 6 – 24 months infants and young children in African communities - De Kock, Henrietta Letitia (University of Pretoria, 2020)
Thesis (PhD (Food Science))--University of Pretoria, 2020.